The Insoluble Protein Deposit (IPOD) in Yeast - Rothe, Stephanie; Prakash, Abaya; Tyedmers, Jens (Frontiers in Molecular Neuroscience, 2018)
The appearance of protein aggregates is a hallmark of several pathologies including many neurodegenerative diseases. Mounting evidence suggests that the accumulation of misfolded proteins into inclusions is a secondary line of defense when the extent of protein misfolding exceeds the capacity of the Protein Quality Control System, which mediates refolding or degradation of misfolded species. Such exhaustion can occur during severe proteotoxic stress, the excessive occurrence of aggregation prone protein species, e.g. amyloids, or during ageing. However, the machinery that mediates recognition, recruitment and deposition of different types of misfolded proteins into specific deposition sites is only poorly understood. Since emerging principles of aggregate deposition appear evolutionarily conserved, yeast represents a powerful model to study basic mechanisms of recognition of different types of misfolded proteins, their recruitment to the respective deposition site and the molecular organization at the corresponding site. Yeast possesses at least 3 different aggregate deposition sites, one of which is a major deposition site for amyloid aggregates termed Insoluble PrOtein Deposit (IPOD). Due to the link between neurodegenerative disease and accumulation of amyloid aggregates, the IPOD is of particular interest when we aim to identify the molecular mechanisms that cells have evolved to counteract toxicity associated with the occurrence of amyloid aggregates. Here, we will review what is known about IPOD composition and the mechanisms of recognition and recruitment of amyloid aggregates to this site in yeast. Finally, we will briefly discuss the possible physiological role of aggregate deposition at the IPOD.